INVESTIGATING ONLINE SPEAKING ANXIETY FACTORS AMONG L2 LEARNERS IN INSTITUTIONAL CONTEXTS DURING COVID- 19 PANDEMIC - Nahid Hassanipour M.A.; Azadeh Nemati Ph.D.; Amin Marzban Ph.D.; Hamidreza Hassanipour M.D. (Adisam Publisher, 2025)
This study set out to investigate online speaking anxiety factors among institute L2 learners during the Covid-19 pandemic. It also investigated whether there is any significant difference between females and males’ anxiety or not. The participants comprised 50 male and female L2 learners in Shiraz language institutes, aged 14 to 27, with varying English proficiency levels selected through non- probability sampling of the convenience type. Mc Croskey questionnaire was used for data collection. The collected data were analyzed and interpreted by the researcher using SPSS software (version 24) along with the assessment of data normality. Based on the results of the research, factors such as lack of readiness, personality, fear of speaking in class, fear of negative evaluation, and getting tense and nervous cause speaking anxiety among institute L2 learners during the Covid-19 pandemic. Notably, a significant gender difference was observed only in the components